Influence of a double vortex chamber on temperature reduction in a counter-flow vortex tube - Samruaisin, P.; Chuwattanakul, V.; Pimsarn, M.; Promthaisong, P.; Saysroy, A.; Chokphoemphun, S.; Kumar, M.; Eiamsa-ard, S. (My University, 2021)
This article reports the effect of double vortex-chambers with multiple inlet snail entries of N = 1, 4 and 6 nozzles on the energy separation referred to cold gas exit temperature difference (ΔTc) in a counter-flow vortex tube type. The experimental work focused on ascertaining the effects of entry air pressure (Pi = 2, 3 and 4 bar), distance ratios between the two vortex-chamber to the vortex tube diameter (l/D = 0.875–1.125) and the cold gas mass ratio (μc) in a vortex tube. It was found that cold gas exit temperature difference (ΔTc) increased with increasing inlet air pressure (Pi) and number of inlet nozzles (N), and decreasing l/D. Among the studied conditions, the double vortex-chamber operated at the highest Pi of 4 bar, N = 6, the smallest l/D = 0.875 and μc = 0.38 gave the highest cold gas exit temperature difference (ΔTc) of 31.5 °C. In addition, the deep learning optimization technique was also developed to predict the temperatures for different combination of parameters used in this study. It was found that the optimal models provide maximum R2 value of 0.99317.
Keywords: Cold gas exit temperature difference (ΔTc); Counter-flow vortex tube type; Deep learning; Double vortex-chambers; Ranque-hilsch vortex tube (RHVT)